Determination of Guanfacine in Oral Fluid and Serum of Children and Adolescents with Attention-Deficit/Hyperactivity Disorder: A Short Communication. Issue 2 (April 2022) - Wohkittel, Christopher; Scherf-Clavel, Oliver; Fekete, Stefanie; Romanos, Marcel; Högger, Petra; Gerlach, Manfred
Abstract : Background: Guanfacine, a selective α2A -adrenoreceptor agonist, is a second-line medication for treating children and adolescents with attention-deficit/hyperkinetic disorder. The dosage administered as milligram per body weight to balance the potential benefits and risks of treatment. Therapeutic drug monitoring (TDM) is useful for identifying a patient's therapeutic window to optimize individual drug dosing and reduce the risk of adverse drug reactions. However, in children and adolescents, intravenous sample collection is especially stressful and thus remains a primary challenge, restricting the use of TDM. Therefore, evaluating alternative specimens to facilitate TDM is a worthwhile task. The aim of this study was to assess the feasibility of using oral fluid for TDM of guanfacine in children and adolescents. Methods: In this article, 9 patients (median age 8.1 years; 6 boys and 3 girls) undergoing treatment with guanfacine were included. Simultaneously collected oral fluid and serum samples were deproteinized using methanol containing a stable isotope-labeled internal standard before the determination of guanfacine by liquid chromatography–tandem mass spectrometry. Pearson correlation and paired t test were used for statistical analysis. Results: The mean serum guanfacine concentration was 3 times higher than that detected in oral fluid (7.47 ng/mL versus 2.36 ng/mL; t (8) = 5.94; P < 0.001). A strong positive linear correlation ( r = 0.758, P = 0.018) was identified between oral fluid and serum concentrations. A strong but nonsignificant negative correlation ( r = −0.574, P = 0.106) was detected between the oral fluid pH and oral fluid-to-serum concentration ratio. Conclusions: The strong correlation between oral fluid and serum concentration and the probable small effect of oral fluid pH on oral fluid-to-serum concentration ratio supports guanfacine as a suitable candidate for TDM in oral fluid.